Evolution of raw meat polarization‐based properties by means of Mueller matrix imaging. Issue 5 (28th December 2020) - Peyvasteh, Motahareh; Popov, Alexey; Bykov, Alexander; Pierangelo, Angelo; Novikova, Tatiana; Meglinski, Igor
Abstract: The possibilities of using Mueller matrix (MM) imaging polarimetry to assess meat quality have not yet been sufficiently explored. In the current study, the fresh porcine muscles are imaged at room temperature with a wide‐field MM imaging polarimeter over 26 hours to visualize dynamics of tissue optical properties through applying Lu‐Chipman decomposition. The frequency distribution histograms (FDHs) and statistical analysis of the MM elements show prominent changes over time. The wavelength spectra of both total depolarization and scalar retardance have dips at 550 nm whereas their values continuously increase with time; the former is referred to the increase of number of scattering events and decrease of myoglobin absorption in the red part of visible spectra related to meat color and freshness, while the latter is associated with the increase in birefringence and meat tenderness. The obtained results are promising to develop a novel fast noncontact optical technique for monitoring of meat quality. Abstract : Here, dynamics of the porcine tissue optical properties over time have been visualized through using Mueller matrix imaging polarimetry. Total depolarization and retardance spectra have dips at 550 nm referred to myoglobin absorption drop (and meat color changes) and increase in birefringence and toughness, respectively. Furthermore, statistical moment's analysis of FDHs demonstrates the potential to give a quantitative metrics to assess meat quality with time. The results are promising for a novel approach for monitoring meat quality.